Effect of Gibberellin Responsive Reduced Height Allele Rht13 on Agronomic Traits in Spring Bread Wheat in Field Experiment in Non-Black Soil Zone - Mikhail G. Divashuk; Pavel Yu. Kroupin; Sergey Yu. Shirnin; Milena Vukovic; Aleksandra Yu. Kroupina; Gennady I. Karlov (Agronomy, 2020)
The introduction of gibberellin-responsive reduced height (GAR Rht) alleles is a promising tool for breeding semi-dwarf, high-input varieties of wheat. We have compared recombinant isogenic lines F2:3 carrying dwarfing allele Rht13 and without dwarfing alleles, obtained from the cross of isogenic lines and selected from F2 using molecular markers. After phenotyping and statistical analysis, we found that the Rht13 allele reduces total plant height by 13.0 cm (17.4%), while the proportions between the internodes in tall and short plants remain similar. The greatest decrease in length in plants with Rht13 in comparison to wild-type plants is observed for the second internode (5.3 cm, or 31.9%). Due to the presence of Rht13, semi-dwarf plants, compared to the wild type, had a higher grain number per main spike, grain number per spikelet and higher number of productive tillers, and a slightly higher harvest index, although thousand grain weight and grain weight in the main spike were lower. Our results indicate the possibility of using Rht13 in the breeding of wheat varieties without dramatic negative effects on yield and plant development.